(untitled) (Herald of Journalism, 2016)
From the earliest days of the Soviet system power declared its commitment to democracy. Foundation of the economy of democratic society was the proclamation of public ownership of the land and the means of production. In the first constitution of the Kazakh SSR, adopted by Kazakh Congress of Soviets in late March 1937, the republic was defined as a socialist state of workers and peasants, in which all the fullness of power belongs to the workers. Economic bases of the Kazakh SSR, was recognized the socialist economic system and public ownership of the means of production. Private appropriation has been replaced by a general distribution. As a result, those who stood at the distribution actually turned into the new owners of the land and the means of production and received the right to dispose of the fruits of labor. Abolition of private property eventually led to a total nationalization of all social life, and that was the beginning of the establishment of the administrative-command system. Understanding the issues of history newly independent Republic of Kazakhstan plays an important role in the formation of the new state of the country is directly related to the activities of its press. In this sense, the study of the history of the Kazakh people of its national characteristics, and their media coverage is of particular importance for the entire course of the transformation process and to assess the economic, social and cultural policy of the country. According to this need of the modern history of sovereign country in-depth analysis of issues and not only its economic and political life, but also to study the general problems of the republic, including the activities of national journalism.